Psychological Well-being of Adolescents in the Aisyiyah Kudus Orphanage as Viewed from Social Support and Self-Efficacy - Annisa Nurusshofa; Mohammad Khasan (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to determine the relationship between social support and self-efficacy with psychological well-being among adolescents living in Aisyiyah Orphanage Kudus. The participants were 80 adolescents aged 16–22 who had resided in the orphanage for over 10 years. The proposed hypotheses stated that both social support and self-efficacy are positively related to psychological well-being. This quantitative research employed a correlational survey method with purposive sampling. Instruments included three Likert-based psychological scales for each variable. Data were analyzed using multiple linear regression and Pearson correlation through SPSS version 26. The results indicated no significant relationship between social support and self-efficacy with adolescents' psychological well-being, leading to the rejection of both major and minor hypotheses. Nevertheless, most participants were in the moderate category across all variables, suggesting a relatively stable yet suboptimal psychological condition.